Economic freedom in Algeria and its role in attracting foreign direct investment - Anter KAHLAT; Kamel CHERAYETT (Dirassat Journal Economic Issue, 2024)
This study aims to highlight the role of economic freedom in attracting foreign direct investment (FDI) in Algeria. It utilizes four international indices that measure various aspects of economic freedom and assess the suitability of the business climate for investment by analyzing Algeria's performance in these indices. The study finds that the volume of FDI flows is positively correlated with the degree of economic freedom. This is because economic freedom provides a favorable, stimulating, and encouraging environment for investors and companies to invest their money in the economy. Algeria's performance has been weak in most of the indices, indicating that it suffers from a low level of economic freedom. This reflects an investment climate that is not qualified to business operations and discourages FDI, with restrictions that limit economic activity and the freedom of individuals and companies to conduct their business